High prevalence of spondyloarthritis and ankylosing spondylitis among familial Mediterranean fever patients and their first-degree relatives: further evidence for the connection - Akar, Servet (BioMed Central, 2013)
INTRODUCTION: Familial Mediterranean fever (FMF) is an auto-inflammatory disease characterized by recurrent attacks of fever and serositis. Limited data suggest that the prevalence of sacroiliitis is increased in patients with FMF. In our present study, we assessed the prevalence of spondyloarthritis (SpA), including ankylosing spondylitis (AS), among a cohort of FMF patients and their unaffected first-degree relatives (FDRs). METHODS: The current study cohort comprised a consecutive group of 201 unrelated patients with FMF and 319 FDRs (≥ 16 years old). These subjects were examined according to a standard protocol. RESULTS: A total of 157 FMF patients (78.1%) and 233 (73%) unaffected FDRs reported back pain. Fifteen FMF patients (7.5%) and nine unaffected FDRs fulfilled the modified New York (mNY) criteria for AS. One additional FDR with AS was identified after review of the medical records. None of the FMF patients with AS was HLA-B27 positive. The allele frequency of M694V among the FMF patients with radiographic sacroiliitis was significantly higher in comparison with those without sacroiliitis (OR 4.3). When compared with the general population, the risk ratios for SpA and AS among the FDRs of our FMF patients were 3.3 (95% CI; 2.0 to 5.5) and for AS 2.9 (95% CI; 1.3 to 6.4), respectively. CONCLUSIONS: Our study suggests that a) factors other than HLA-B27 play a role in the association of FMF and SpA/AS; b) MEFV gene variations may be one of the geographic/region-specific potential pathogenetic links between these two disorders in the Turkish population.